Sistema FOQuE para expansão semântica de consultas baseada em ontologias difusas - Yaguinuma, Cristiane Akemi (2007)
As availability of data from several areas of knowledge grows, it is even more necessary to develop effective techniques to retrieve the desired information, aiming to reduce irrelevant answers and ensure that relevant results are not ignored. Considering this context, we present the FOQuE system, developed to perform query expansion in order to retrieve semantically relevant and broad results. Based on fuzzy ontologies, this system is able to obtain approximate results that satisfy user requirements according to expansion parameters defined by the user. The additional answers retrieved by the FOQuE system are classified according to the semantic expansion performed and the relevance to the query, therefore it is possible to improve results that are presented to the user.